The Implementation of the Native English Program at Madrasah Ibtidaiyah Masjid Nasional Al-Akbar Surabaya - Faridatul Aliyah; Henny Merizawati (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
This study seeks to investigate the implementation of the Native English Program at Madrasah Ibtidaiyah Masjid Al-Akbar Surabaya as an innovation in English learning at Madrasah Ibtidaiyah Masjid Nasional Al-Akbar Surabaya level. A descriptive qualitative approach was used to deepen understanding of implementation, effectiveness, obstacles encountered, and strategies adopted. Data collection was carried out through participatory observation and semi-structured interviews with one the madrasah principal, one cordinator program, four native English teachers, four local teachers, and four out of 100 students. They was consistently reported to improve students' communicative competence and classroom participation. This research is unique and important because there is still limited previous literature found by researchers regarding this issue. Despite the growing adoption of native English- teachers in language education, limited research has examined how such programs are implemented in Madrasah Ibtidaiyah and how they integrate religious values with authentic language learning. The findings extend the literature on bilingual and internationalized language education in faith- based schools and offer practical guidance for institutions seeking to implement sustainable native-speaker programs. The implementation of this program runs in a sustainable manner through collaborative support between native English teachers and local teachers. The obstacles faced included the limited quantity of native English teachers, the differences in teaching approaches, and the psychological readiness of students. The problem-solving strategies implemented included a continuous mentoring program, standardization of learning methodologies, pre-learning language orientation, and evaluation of monitoring mechanisms through the Fun Education approach. These results made a substantial contribution to the development of relevant, authentic, and globally oriented English learning innovations at Madrasah Ibtidaiyah Masjid Nasional Al-Akbar Surabaya level.